Marian MacDowell papers - MacDowell, Marian, 1857-1956.; MacDowell, Edward, 1860-1908.; Richardson, Nina Maud.; Edward MacDowell Association
Correspondence, writings, clippings and other printed material, memorabilia, and other papers relating primarily to MacDowell's activities with the MacDowell Colony, the artists' community in Peterborough, N.H., established to honor her husband. Includes Edward MacDowell's letters to his wife, musical scores, and other personal and family papers (1890-1904); records of the Edward MacDowell Association, Inc., a New York-based foundation that financed and administered the colony; and papers of Nina Maud Richardson, including her correspondence with Marian MacDowell and with Van Wyck Brooks, O. Louis Guglielmi, Hermann Hagedorn, and Jean Starr Untermeyer. Marian MacDowell's correspondents include Aaron Copland, Theodore Dreiser, Daniel Chester French, Hamlin Garland, DuBose Heyward, Archibald MacLeish, Nina Maud Richardson, Edwin Arlington Robinson, Augustus Saint-Gaudens, Roger Sessions, Upton Sinclair, and Thornton Wilder.
Library of Congress Music Division.
Philanthropist, musician, and cofounder of the MacDowell Colony, Peterborough, N.H. Born Marian Griswold Nevins; married composer Edward MacDowell (1861-1908) in 1884.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Brooks, Van Wyck, -- 1886-1963 -- Correspondence; Copland, Aaron, -- 1900-1990 -- Correspondence; Dreiser, Theodore, -- 1871-1945 -- Correspondence; French, Daniel Chester, -- 1850-1931 -- Correspondence; Garland, Hamlin, -- 1860-1940 -- Correspondence; Guglielmi, O. Louis -- 1906-1956 -- Correspondence; Hagedorn, Hermann, -- 1882-1964 -- Correspondence; Heyward, DuBose, -- 1885-1940 -- Correspondence; MacLeish, Archibald, -- 1892-1982 -- Correspondence; Robinson, Edwin Arlington, -- 1869-1935 -- Correspondence; Saint-Gaudens, Augustus, -- 1848-1907 -- Correspondence; Sinclair, Upton, -- 1878-1968 -- Correspondence; Untermeyer, Jean Starr, -- 1886-1970 -- Correspondence; Wilder, Thornton, -- 1897-1975 -- Correspondence; MacDowell Colony (Peterborough, N.H.); Artist colonies -- New Hampshire -- Peterborough; Musicians; Philanthropists